Analisis Kinerja Keuangan PT AKR Corporindo Tbk Sebelum dan Sesudah Melakukan Joint Venture - Wilantari, Adela; Anita, Widya Febryari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
This study was conducted to determine and analyze the financial performance of PT AKR Corporindo Tbk. before and after conducting a joint venture as measured using profitability financial ratios consisting of Return On Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM). The data used in this study comes from the quarterly consolidated financial statements of PT AKR Corporindo Tbk for the 2013 to 2021 obtained from the official website of the Indonesia Stock Exchange (IDX). Data analysis in this study uses SPSS version 29.0 tools to test data by conducting normality test and the dependent sample t-test. In addition, an analysis was carried out by assessing and comparing the results of financial ratios calculations before and after conducting a joint venture. The results of the study after the SPSS test showed that there were no significant difference in the data used in the study before and after conducting a joint venture, with the results of the analysis at PT AKR Corporindo Tbk after conducting a joint venture is experiencing differences in the level of financial performance, where after conducting a joint venture, PT AKR’s profit continues to increase so that it can be considered effective, which can be seen from the company’s ability to manage costs that need to be incurred properly so that it continues to obtain a large enough operating profit.